HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PENCEGAHAN PENULARAN TB PARU PADA MANTAN PENDERITA TB PARU DI WILAYAH KERJA PUSKESMAS SUNGAI DURIAN KABUPATEN KUBU RAYA - ., Wasis Setyo Bowo (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background: National TB program states that community involvement inTB cases is very important. One of the components in society which canbe involved is former TB patients. The involvement of former TB patient tochange community behavior about TB can be done by providingknowledge about TB disease. Objective: To determine the relationshipbetween knowledge level and attitudes towards TB transmissionprevention behavior of former TB patients in primary health center SungaiDurian Kubu Raya. Methodology: This research method was analyticswith cross sectional approach conducted with questionnaires to formerpulmonary tuberculosis patients in primary health center Sungai DurianKubu Raya. Results: There were 34 people who met the study criteria; 15men and 19 women. Measured variables have a statistically significantrelationship, measured by Fisher test. Conclusion: There is a relationshipbetween the knowledge level and attitudes towards TB transmissionprevention behavior of former TB patients in primary health center SungaiDurian Kubu Raya.Keywords: Tuberculosis. Knowledge. Attitude. Behavior